EXPRESSIVE SPEECH ACTS OF INSTAGRAM INFLUENCERS IN PROMOTING GOODS AND SERVICES AND THEIR IMPLICATIONS FOR ADVERTISEMENT TEXT MATERIALS - Nurmadiah, Ira; Tressyalina, Tressyalina (Universitas Muhammadiyah Makassar, 2025)
This research is motivated by the use of language by influencers (selebgram) in promoting products and services, which is considered to help students in writing advertisement texts. This study aims to explain the expressive speech acts of influencers in promoting products and services and their implications in advertisement text materials, focusing on: (1) the forms of expressive speech acts, (2) the strategies of speech, and (3) the implications of their use in advertisement text materials. This research uses a qualitative descriptive method, with data derived from the speech acts of influencers on the personal Instagram accounts of DA, MI, and RV from July to November 2024. Data collection was done through media review techniques by downloading promotional post recordings, which were then identified and classified according to the research objectives. Data validation used triangulation techniques, while data analysis was carried out in three stages: analysis, discussion, and conclusion. The results of the study revealed three main findings. First, four types of expressive speech acts were found: praising, thanking, apologizing, and congratulating. Second, two speech strategies were used: positive politeness and negative politeness strategies. These findings indicate that expressive speech acts of praising and the direct speech strategy with positive politeness were more dominant, creating polite and effective utterances for advertisement texts. Third, these forms and strategies of expressive speech acts can be used as teaching materials for writing advertisement texts.